THE CONCEPT OF MUDHARABAH CONTRACT AND ITS APPLICATION TO SHARIA SECURITIES CROWDFUNDING IN INDONESIA - Muhammad Fahmi Akbar (Al-Maslahah : Jurnal Ilmu Syariah, 2022)
This article discusses the concept of the Mudharabah contract and its application to Sharia securities crowdfunding in Indonesia. The article has a discussion focus related to issues regarding Mudharabah which have developed both from the implementation and the provisions in it. The method used in this study is a descriptive method with a qualitative approach. The data sources used come from books, books, journals, the internet, and so on that are relevant to the subject matter. The results of the research in the article are: First, the majority of scholars define mudhrabah based on their own understanding which when the common thread is drawn that mudharabah is a cooperation contract between two parties in which one party gives his property to another party to be traded. Scholars agree on the permissibility of the mudharabah mutlaqoh contract but differ in opinion regarding the mudharabah muqayyadah which the Shafi'iyyah scholars and Maliki scholars consider invalid. The majority of scholars agree that the pillars of the mudharabah contract consist of 'aqidain, ma'qud and shighat akad Second, securities crowdfunding is a method of raising funds with a joint venture scheme carried out by business owners to start or develop their business and Sharia securities crowdfunding is crowdfunding of securities based on the principle of -Shariah principles. Third, the implementation of the mudharabah contract on Sharia securities crowdfunding in Indonesia has been carried out by several platforms, one of which is Shafiq which issues sukuk based on the mudharabah contract whose implementation is in harmony with the opinions of scholars, and the DSN-MUI fatwa.